Impact of the 3-D structure on the photovoltaic potential in Urban areas - Shouchao, Hu; Dong, Li; Zengliang, Chang; Hongju, Tong; Xingguo, Gao; Qian, Cao (Frontiers in Energy Research, 2025)
IntroductionWith the acceleration of urbanization and the continuous growth in energy demand, distributed photovoltaic (PV) systems have attracted increasing attention as a sustainable energy solution. In practical deployment, the 3-D structure of buildings significantly affects their photovoltaic potential.MethodsTo more comprehensively assess the underlying mechanism, this study employs ENVI-met to conduct daily-scale solar irradiance simulations on seven building models across three typical urban block types. The 3-D characteristics of buildings are characterized from two perspectives: urban block type and three-dimensional structural parameters. The analysis covers four radiation components: total radiation, direct radiation, diffuse radiation, and reflected radiation. To enhance the real-world applicability of the study, LiDAR-derived real 3-D building models are introduced, and surface radiation distributions are simulated for the full year as well as for typical solar terms (Summer Solstice, Winter Solstice, and Spring/Autumn Equinox).ResultsDaily-scale simulation results indicate significant differences in photovoltaic potential among different building layouts. Central-type blocks exhibit the most favorable irradiance performance under conditions of moderate building height, appropriate spacing, and balanced Sky View Factor; vertical-type blocks rank second; while hybrid-type blocks, despite having higher rooftop area ratios and coverage ratios, suffer from severe shading effects due to staggered building heights, resulting in the lowest photovoltaic potential. Full-year scale simulation results using LiDAR-derived real 3-D building models show strong consistency with the daily-scale models in identifying optimal building types, verifying the consistency of the influence mechanism of building structures on photovoltaic potential across different temporal scales.DiscussionThe results confirm that, even when accounting for environmental obstructions such as vegetation, central-type structures retain a stable advantage in solar energy generation. This study provides both theoretical support and practical guidance for the scientific deployment of urban photovoltaic systems.